Model pengukuran religiusitas, budaya lingkungan dan kepercayaan pada otoritas pajak terhadap kepatuhan wajib pajak UMKM - Nurindah Salma Fitriyah; Yanti Yanti; Trias Arimurti (LPMP Imperium, 2024)
This research is very important to do because there is a very low decline in the number of Annual Tax Return reporting from the number of registered MSMEs in 2022-2023 caused by several factors such as religiosity, environmental culture and trust in tax authorities. The purpose of this study is to evaluate the effects of religiosity, environmental culture and trust in tax authorities. The approach used in this research is quantitative. The data needed for this research is primary data, obtained from google forms and distributed to MSMEs in Karawang Regency. The population in the study was 17,760 MSMEs recorded at KPP Pratama Karawang in 2023. The sample was taken utilizing purposive sampling so that 100 taxpayers were obtained with predetermined criteria according to the needs of the researcher. The test tool in the study used SmartPLS 3.0. The results of this study show that first, religiosity has no effect on MSME taxpayer compliance. Second, environmental culture affects MSME taxpayer compliance. Third, trust in tax authorities affects MSME taxpayer compliance.